2014
DOI: 10.1038/ncomms4690
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of listeriolysin O reveals molecular details of oligomerization and pore formation

Abstract: Listeriolysin O (LLO) is an essential virulence factor of Listeria monocytogenes that causes listeriosis. Listeria monocytogenes owes its ability to live within cells to the pH-and temperature-dependent pore-forming activity of LLO, which is unique among cholesteroldependent cytolysins. LLO enables the bacteria to cross the phagosomal membrane and is also involved in activation of cellular processes, including the modulation of gene expression or intracellular Ca 2 þ oscillations. Neither the pore-forming mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(182 citation statements)
references
References 57 publications
9
170
0
Order By: Relevance
“…S1). These data are consistent with suggestions that charge complementarity between perforin monomers may drive initial oligomerization events (33,34).…”
Section: Phylogenetic Analysis Reveals That Sntx Represents An Anciensupporting
confidence: 92%
“…S1). These data are consistent with suggestions that charge complementarity between perforin monomers may drive initial oligomerization events (33,34).…”
Section: Phylogenetic Analysis Reveals That Sntx Represents An Anciensupporting
confidence: 92%
“…It was shown that at neutral pH, the charge repulsion of these carboxylates caused the premature unfurling of the ɑHBs into β-hairpins in the soluble LLO monomers: restraining the unfurling of αHB1 by tethering it to D2 through an engineered disulfide slowed the pH-dependent inactivation. Recently, the predicted acidic triad carboxylate structure was confirmed when LLO was crystalized and its structure was solved [4]. Thus, unfolding of the ɑHBs serves dual functions in LLO: in the context of the phagosome, the ɑHBs unfold and transition to TMHs following the normal pore-forming mechanism.…”
Section: Dual-functional Tmhs In Llo From Listeria Monocytogenesmentioning
confidence: 97%
“…Although D4 was initially shown to interact between PFO monomers [54,55], subsequent studies indicated that D4 remains surrounded by water throughout the assembly of the pore [19,56]. More recently, however, Pokrajac et al [57] and Koster et al [4] showed that purified D4 from pyolysin and LLO, respectively, was capable of forming linear oligomeric arrays on liposomes. In contrast to the earlier work of Tweten et al [54] and Iwamoto et al [58] who showed an inhibitory effect of D4 on native toxin, Pokrajac et al showed that D4 increased pyolysin activity.…”
Section: Allosteric Pathway For Monomer Activationmentioning
confidence: 99%
See 2 more Smart Citations